PLURALITAS AGAMA MENURUT PANDANGAN TOKOH-TOKOH AGAMA DAYAK DI DESA KAPUL KECAMATAN HALONG KABUPATEN BALANGAN - abdul hamid (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2017)
Religious plurality is condition which no one can reject it but it must be thought how to respond the issue. So far, many recorded attitude show various respond about it. This work will elaborate the issue from religious people’s perspective, especially the figures in Kapul village, Halong districts of Balangan regency. Actually, it is Dayak’s region. But, there are many religious followers such Islam, Catholics, Hinduism, Buddhism, and local religion. They live together in harmony. This research is a qualitative one with sociological approach as the main theory of Max Weber’s charismatic. While the methods are direct observation, interview, and documentation.It concluded that Dayak figures believe that everyone can choose their religion without force and pressure so then they can respect another highly. Even in the village, every community will attend an event that hold by other religious communities. They believe that all of them are originated from the same ancestor so religion cannot change this principle.